Gender inequality as a barrier to economic growth: a review of the theoretical literature - Manuel Santos Silva; Stephan Klasen (Review of Economics of the Household, 2021)
In this article, we survey the theoretical literature investigating the role of gender inequality in economic development. The vast majority of theories reviewed argue that gender inequality is a barrier to development, particularly over the long run. Among the many plausible mechanisms through which inequality between men and women affects the aggregate economy, the role of women for fertility decisions and human capital investments is particularly emphasized in the literature. Yet, we believe the body of theories could be expanded in several directions.
Keywords: 330; E20; J13; J16; J24; O11; O41; Gender equality; Economic growth; Fertility; Human capital; Comparative development